Green synthesis of nickel ferrite nanoparticles using starch for visible-light photocatalytic degradation of crystal violet - Do, Mai Nguyen; Vo, Chau Ngoc Anh (Hue University Journal of Science: Natural Science, 2025)
This study presents the green synthesis of NiFe₂O₄ nanoparticles with starch as a reducing and stabilising agent. The material was characterised with XRD, FT-IR, SEM, TEM, BET, and UV–Vis DRS, confirming a spinel structure, mesoporosity (58.3 m²/g), uniform spherical morphology (10–20 nm), and a band gap of 2.54 eV. Photocatalytic degradation of crystal violet under visible light achieved a 76.0% efficiency within 120 minutes, following pseudo-first-order kinetics. Compared with other photocatalysts, NiFe₂O₄ exhibits superior activity. The starch-mediated green synthesis improved dispersion and photocatalytic performance, offering a sustainable route for efficient visible-light-driven photocatalysts in environmental remediation.